MATERIALISME : PENYEBAB DAN KONSEKUENSI - Fransisca Mulyono (Center for Economic Studies Universitas Katolik Parahyangan, 2011)
Materialism defined as the importance a person places on possessions and their acquisition as a necessary or desirable form of conduct to reach desired end states, including happiness. It has certain negative effects : increasing risk for diminished well-being (happiness) afterwards lead to negative subjective well-being, low level se/f- determination, low level gratitude and negative meaning in life. This is a phenomenon have been around everywhere and everyone: kids, teenagers even adults, emerging because of ever increasing the symbolic consumption, not utilitarian consumption. Some researchs showed that there are some causes be responsible for materialism: dominant social paradigm, peer group pressure, and conspicuous consumption. Concerning its negative effects, socialization process about materialism must be done to everybody comprehensively.